Level of Preference microbiological activity on Facial Hydrating Toner Preparations from Seaweed (Turbinaria conoides) with the Addition of Centella asiatica Leaf Extract (Pegagan) - Nadilah, Fani; Surilayani, Dini; Pratama, Ginanjar (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This study aims to determine the level of consumer preference and microbiological activity of the formulations of T. conoides and C. asiatica in hydrating toner preparations. Hydrating toner preparations are the easiest and cheapest cosmetics to make, so they can be the initial stage of research in determining consumer preferences. The stages of this research were preparation of T. conoides, extraction of C. asiatica, formulation and hedonic scale testing and microbiological activity. The parameters tested were comparisons between T. conoides and C. asiatica 1:1 (F1), 2:1 (F2), 1:2 (F3) and preparations without these ingredients (F0). The results of the research on the aroma, F1 is least preferred. The color parameter most preferred panelists is F0. F3 was the most preferred hydrating toner by the panelists for the sticky feeling and the favorite parameter with the most preferred toner is F3. The results of microbial activity F0, F1 & F2 are not suitable for use because they have more than 105 contaminants and F3 are still safe to use, therefore F3 was the best based on the tests performed.